IMPROVING PATIENT SAFETY CULTURE (PSC) IN PRIMARY HEALTH CENTERS IN JAMBI PROVINCE - Guspianto, Guspianto; Nurlinawati, Nurlinawati; Pramudiani, Dessy (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2025)
Background: Patient safety incidents continue to occur in primary health care services despite being 24% to 85% preventable. Promoting and assessing patient safety culture is the primary step to minimize and prevent adverse incidents. Aims: This research examined the level of patient safety culture implementation in Primary Health Centers. Methods: A quantitative descriptive research design was conducted involving 319 employees randomly selected from 11 Primary Health Centers in Jambi province. Data were collected using the Hospital Survey on Patient Safety Culture (HSOPSC) questionnaire and analyzed descriptively, with an average cut-off point of 75%. Results: The implementation level of patient safety culture in the Primary Health Centers in Jambi Province was 71.5%. Furthermore, seven dimensions of patient safety culture were weakly implemented: staffing, communication openness, organizational learning for continuous improvement, supervisor/manager expectations and actions promoting patients, non-punitive response to error, general perception of patient safety, and frequency of error reporting. Conclusion: Continuous examination should be conducted to ensure better changes in improving patient safety culture. Keywords: Jambi Province, Patient safety culture, Primary health center